Supply chain landscape of 3D printed buildings. A stakeholder decision suppot framework - Ma J; Samarasinghe DAS; Rotimi JOB; Zuo K (MDPI (Basel, Switzerland), 2024)
With the development of new construction technology, increasing attention is being paid to 3D printing due to its construction efficiency as well as its sustainability. Numerous researchers have determined its benefits in cost reduction, resource savings, safety assurance, etc. Although various advantages have been identified, there are limitations and challenges in technology implementation. Especially since it is a new construction method, 3D printing construction projects will have a very different supply chain compared to traditional projects. As part of a research programme investigating the 3D printing construction supply chain in a New Zealand context, this study systematically analysed the research about 3D printing adoption and supply chain challenges in the construction sector. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was adopted as the guideline for literature selection. PRISMA is designed to assist researchers in reporting the review research focus and methodology, and examining the findings from published literature. NVivo was then adopted to code and analyse the selected publications to gather the data necessary for our study. The literature was analysed from the perspectives of the research focus, research methods, and findings. Studies about 3D printing implementation, benefits and barriers, as well as its significance are also analysed. As a result, this research found existing research gaps, including the fragmented situation of management-related research in the 3D printing construction sector, insufficient research in top management for 3D printing construction implementation, and changes to supply chain management practices in 3D printing construction projects. A decision support system demo for supply chain management is drafted in this paper, which requires further study. The research outcome highlighted the existing studies in 3D printing construction implementation and supply chain, and initiated a research topic on supply chain decision making. The result contributes to the theoretical and practical development of 3D printing technology in the construction industry. This review paper also inspires future studies on supply chain frameworks and theoretical models.
Keywords: supply chain management; 3D printing; construction industry